Base Erosion, Profit Shifting and Developing Countries - Crivelli, Ernesto (IMF Working Papers; Working Paper, 2015)
International corporate tax issues are prominent in public debate, notably with the G20-OECD project addressing Base Erosion and Profit Shifting ('BEPS'). But while there is considerable empirical evidence for advanced countries on the cross-country fiscal externalities at the heart of these issues, there is almost none for developing countries. This paper uses panel data for 173 countries over 33 years to explore their magnitude and nature, focusing particularly on developing countries and applying a new method to distinguish between spillover effects through real decisions and through avoidance -and quantify the revenue impact of the latter. The results suggest that spillover effects on the tax base are if anything a greater concern for developing countries than for advanced-and a significant one.